Gestión de un sistema de información y su efecto en el nivel de incidencias en los mantenimientos de redes satelitales de la empresa EDUCOM S.A.C. CM-TARAPOTO - Visalot Fernández, Llilmer (2014)
This thesis entitled "MANAGEMENT INFORMATION SYSTEM AND ITS EFFECT ON THE LEVEL OF INCIDENTS IN THE MAINTENANCE OF SATELLITE NETWORKS ENTERPRISE SAC EDUCOM CM-TARAPOTO "; general objective, improve the level of incidents in the satellite network maintenance company CM-TARAPOTO EDUCOM SAC. It has the specific objectives; value the current level of incidents in the maintenance of the company SAC Education and Communication; Develop and implement a management information system and ultimately determine the effect of management information system on the level of incidents in the maintenance of satellite networks. For the development of the proposed different methodologies were used. For information gathering techniques of observation, interviews were conducted, as well as review and assessment documents; for the analysis and design methodology Object Oriented considering diagrams UML, the Unified Process and prototyping the PHP programming language is used, each of these tools were taken in order to meet used expectations of the company and minimize costs as they are free to use. Seen the need to determine the level of incidents, and hence greater efficiency in the processes and procedures; this thesis investigates and influences the management of an information system at the level of incidents in the maintenance of satellite networks EDUCOM SAC Company.